2014
DOI: 10.1111/plb.12157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data and ecological niche modelling reveal the phylogeographic pattern ofCotinus coggygria(Anacardiaceae) in China's warm‐temperate zone

Abstract: The phylogeography of common and widespread species helps to elucidate the history of local flora and vegetation. In this study, we selected Cotinus coggygria, a species widely distributed in China's warm-temperate zone. One chloroplast DNA (cpDNA) region and ecological niche modelling were used to examine the phylogeographic pattern of C. coggygria. The cpDNA data revealed two phylogeographic groups (Southern and Northern) corresponding to the geographic regions. Divergence time analyses revealed that diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…Previous phylogeographical studies indicated that C. coggygria is a locally adaptive species with a wide distribution range (Wang et al, 2014b). However, whether adaptive evolution occurred on C. coggygria and whether a key factor drives the process of adaptation are unclear.…”
Section: Adaptive Genetic Variation Driven By Precipitationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous phylogeographical studies indicated that C. coggygria is a locally adaptive species with a wide distribution range (Wang et al, 2014b). However, whether adaptive evolution occurred on C. coggygria and whether a key factor drives the process of adaptation are unclear.…”
Section: Adaptive Genetic Variation Driven By Precipitationmentioning
confidence: 99%
“…Similar to other species in the family Anacardiaceae, C. coggygria has a typical flower disc that is used to attract pollinators. Seed dispersers of many species in Anacardiaceae, including C. coggygria, are birds or mammals (Wang et al, 2014b). Although C. coggygria has efficient transmission mechanisms for seeds and pollen, increasing geographical distances and human activities resulted in a significant genetic differentiation among populations.…”
Section: Spatial Population Genetic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Members of this family in other countries have been investigated for their occurrence (Tien-lu, 1980;Swaminath, 2000;Yi et al,2004;Wang, 2014), chemical composition and their applications (Garcia et al, 1999;Ippen, 1982;Benzi, 2009;Makom, 2010;Ojewole, 2005;Ameyapoh, 2010;Al Sayed, 2010;Murray, 2009;Descamps, 2011) and as well as for their molecular data (Wang et al, 2014;Miller et al, 2001, Pell, 2004Yi, 2008). However, in Sri Lanka, members of this family have been studied for their ecological contributions (Weerakkody, and Parkinson, 2006;Gunatilleke, et al, 2005;Jayasekara, et al, 2003;Ganashan, 1996;Gunatilleke and Gunatilleke, 1991;De Zoysa, et al, 1988;Jayasekera, 1992) and medicinal values (Kankanamalage, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%